The acceptability of a donor human milk bank and donated human milk among mothers in Limpopo Province, South Africa - Tebogo Mampane; Jacqueline E. Wolvaardt (Wiley, 2024)
Abstract Breastfeeding is a crucial public health approach that reduces infant morbidity and mortality by providing essential nutrients and antibodies, and breast milk is easily digested. Breastfeeding and donated milk serve as a preventative measure against necrotising enterocolitis. Additionally, they protect against viruses and nosocomial sepsis. When a birthing parent's own milk is unavailable, alternative enteral nutrition for preterm or low‐birth‐weight infants is either donor human milk (DHM) or artificial formula. This study aimed to understand mothers' acceptance of the donor human milk bank (DHMB) and DHM. A qualitative phenomenological study was conducted in Limpopo Province, South Africa. The study used purposive sampling to select 23 mothers in postnatal and neonatal wards. Data collection was via in‐depth interviews using a semistructured interview guide. Manual data analysis using an interpretative phenomenological analysis (IPA) framework was used to coding. Concepts were grouped to generate themes. Three themes and nine subthemes were generated: (1) DHMBs (2) cultural perspective of DHMB, and (3) health considerations of DHM. Participants were unaware of the DHMB. Hesitancy in accepting DHM due to fear of contracting HIV was observed. Cultural beliefs are an influencing factor for use, while donation was driven by altruistic reasons, preventing waste, helping others and having previously benefited from DHM. The study found that mothers are willing to donate human milk. Willingness to donate can be increased by raising awareness about DHMB and addressing culture and safety concerns at antenatal clinics.